Policing Democracy Overcoming Obstacles to Citizen Security in Latin America - Ungar, Mark (Johns Hopkins University Press, 2011)
2011 Winner of the Charles H. Levine Memorial Book Prize of the International Political Science AssociationLatin America's crime rates are astonishing by any standard-the region's homicide rate is the world's highest. This crisis continually traps governments between the need for comprehensive reform and the public demand for immediate action, usually meaning iron-fisted police tactics harking back to the repressive pre-1980s dictatorships. In Policing Democracy, Mark Ungar situates Latin America at a crossroads between its longstanding form of reactive policing and a problem-oriented approach based on prevention and citizen participation. Drawing on extensive case studies from Argentina, Bolivia, and Honduras, he reviews the full spectrum of areas needing reform: criminal law, policing, investigation, trial practices, and incarceration. Finally, Policing Democracy probes democratic politics, power relations, and regional disparities of security and reform to establish a framework for understanding the crisis and moving beyond it.